The Neural Correlates of Spatial and Object Working Memory in Elderly and Parkinson’s Disease Subjects - Silvia P. Caminiti; Chiara Siri; Lucia Guidi; Angelo Antonini; Daniela Perani (Behavioural Neurology)
This fMRI study deals with the neural correlates of spatial and objects working memory (SWM and OWM) in elderly subjects (ESs) and idiopathic Parkinson’s disease (IPD). Normal aging and IPD can be associated with a WM decline. In IPD population, some studies reported similar SWM and OWM deficits; others reported a greater SWM than OWM impairment. In the present fMRI research, we investigated whether compensated IPD patients and elderly subjects with comparable performance during the execution of SWM and OWM tasks would present differences in WM-related brain activations. We found that the two groups recruited a prevalent left frontoparietal network when performing the SWM task and a bilateral network during OWM task execution. More specifically, the ESs showed bilateral frontal and subcortical activations in SWM, at difference with the IPD patients who showed a strict left lateralized network, consistent with frontostriatal degeneration in IPD. The overall brain activation in the IPD group was more extended as number of voxels with respect to ESs, suggesting underlying compensatory mechanisms. In conclusion, notwithstanding comparable WM performance, the two groups showed consistencies and differences in the WM activated networks. The latter underline the compensatory processes of normal typical and pathological aging.